Higher education: impact of substance use on self-esteem and well-being - Liliana Mendes; Levi Leonido; Bruna Soares; Tânia Guimarães; Cátia Romão; Mariana Guerra; Elsa Maria Gabriel Morgado (Motricidade)
The consumption of psychoactive substances by university students is a subject that has been gaining more and more attention in the literature. However, there is still a lot of disagreement on this subject. This study aims to relate the impact of substance consumption habits (alcohol, tobacco and other psychoactive substances) with self-esteem and psychological well-being in university students, in order to gain a better understanding of this issue. This is a descriptive, cross-sectional, quantitative, correlational study with a quasi-experimental design. The sample consisted of 460 university students aged between 18 and 66 with internet access. Of these participants, 299 were female and 158 were male. The instruments used were a Sociodemographic Questionnaire, the Scale for the measurement of Manifestation of Psychological Well-being (EMMBEP) and the Rosenberg Self-Esteem Scale (RAS). The results showed no statistically significant differences in terms of self-esteem and psychological well-being according to substance use. In addition, only the consumption of other psychoactive substances was significantly higher in male participants than in female participants.